A Carborane‐Derivative "Click" Reaction under Heterogeneous Conditions for the Synthesis of a Promising Lipophilic MRI/GdBNCT Agent1. Issue 2 (14th November 2012) - Toppino, Antonio; Bova, Maria Elena; Geninatti Crich, Simonetta; Alberti, Diego; Diana, Eliano; Barge, Alessandro; Aime, Silvio; Venturello, Paolo; Deagostino, Annamaria
Abstract In this study, the Huisgen reaction has been used to functionalise a carborane cage with a lipophilic moiety and a 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (DOTA) ligand to obtain a new Gd boron neutron‐capture therapy (BNCT)/magnetic resonance imaging (MRI) agent. The introduction of the triazole units has been accomplished under both heterogeneous conditions, by the use of a Cu‐supported ionic‐liquid catalyst, and homogeneous conditions. The ability of the Gd complex of the synthesised ligand to form stable adducts with low‐density lipoproteins (LDLs) has been evaluated and then MRI has been performed on tumour melanoma cells incubated in the presence of a Gd‐complex/LDL imaging probe. It has been concluded that the high amount of intracellular boron necessary to perform BNCT can be reached even in the presence of a relatively low‐boron‐containing LDL concentration.